Building a future on four wheels : An ethnography of locomotive disability in Mitchell's Plain (South Africa) - (:unkn) unknown (My University, 2017)
This thesis explores subjectivities shaped by locomotive disability in the post-apartheid city through an ethnography of ordinary life. Locomotive disability encompasses every limitation of mobility due to an infirmity of the lower limbs. In my discussion, it is conceived as a ‘test’ (épreuve), namely an event that interrupts everyday routines and creates tensions between the responsibilities of different actors’ – people with disabilities, families, the state, etc. These tensions are articulated on various levels. In my discussion, I focus on three of them: the political field that determines a certain type of citizenship, the social networks that constitute the person, and finally the understanding people with disabilities have of their personal history. These levels combine to shape people’s subjectivity, and are analysed in a Foucauldian perspective not just as individuals’ relations with themselves, but also with others and the wider world. Chapter 1 introduces the discussion by providing an overview of the political problematisation of disability in South Africa. I question how national history has influenced discourses and legislation in the field of disability. More specifically, I explore the effects of these programs on the experience of locomotive disability in contemporary South Africa. Chapter 2 then presents in detail South African social security and job creation policies. This section of the thesis introduces an economic dimension to the discussion of the social relationships of people with disabilities which is taken up in the following chapters. Chapter 3 questions significant others’ identity in the process of finding a house. Chapter 4 focuses on gender relationships and their current reconfigurations, as lived by people with disabilities. A third register of sociability is introduced in chapter 5, which documents the existence and the nature of social places in Mitchell’s Plain township and the ways people with
Keywords: African Research